Addressing tuberculosis through complex community-based socioeconomic interventions in low- and middle-income countries: A systematic realist review. Issue 9 (2nd September 2022) - Bustos, Monica; Luu, Kathy; Lau, Lincoln L.; Dodd, Warren
ABSTRACT: The established relationship between poverty and tuberculosis has led to the implementation of complex socioeconomic interventions to address poverty as both a risk factor for and consequence of tuberculosis. However, limited research to date has examined the conditions that facilitate the successful implementation of these interventions. We conducted a systematic realist review to examine how complex socioeconomic interventions for tuberculosis treatment and care were defined, implemented, and evaluated in low- and middle-income countries. We used a systematic search to identify published work that implemented complex socioeconomic interventions for tuberculosis, followed by a realist analysis informed by existing programme theories. From a total of 2825 collected records, 36 peer-reviewed articles and 17 grey literature reports were included in this review. The realist analysis identified three main contexts (sociopolitical and cultural; relational and interpersonal; operational and administrative) and ten mechanisms that facilitated successful implementation of interventions. Overall, this review highlights the importance of political commitment in shaping sustainable programme delivery, the role of healthcare and community-based provider training in creating patient-centred treatment environments, and the opportunity to leverage operational research for evidence-based decision making to address the socioeconomic needs of tuberculosis patients experiencing poverty.